Irinotecan-cholesterol succinic acid simple lipid ion pair, liposome and preparation method and application thereof - GENG SICONG; YAN ZHIQIANG; LUO SHENGGEN; YU LEI; FAN MINGXUE; WANG HAO (2018)
The invention discloses an irinotecan-cholesterol succinic acid simple lipid ion pair, a liposome and a preparation method and application thereof. The cholesterol succinic acid simple lipid is used as a counter-ionic agent, and the active proton of carboxyl in the cholesterol succinic acid simple lipid structure transfers to the nitrogen of irinotecan amino group, a coordination bond is formed, an ion pair is formed with irinotecan, so that the lipid solubility of irinotecan is improved, and the simple preparation method is easily used for packaging the drug on a phospholipid layer of the liposome, and the drug loading and packaging efficiency are improved. According to the irinotecan-cholesterol succinic acid simple lipid ion pair, the liposome and the preparation method and applicationthereof, the hydrophobic ion pair technology is combined with the nano drug delivery system, the lipid solubility of the insoluble drugs is improved, nano-preparations are developed, the complexity ofthe preparation process i